2008
DOI: 10.3920/wmj2007.1012
|View full text |Cite
|
Sign up to set email alerts
|

Gliotoxin natural incidence and toxigenicity of Aspergillus fumigatus isolated from corn silage and ready dairy cattle feed

Abstract: Corn silage is an important feed source for dairy and beef cattle in central Argentina. The presence of thermophilic species Aspergillus fumigatus is among the major problem in silage, as many strains can produce several mycotoxins that affect the health of dairy cattle. The aims of the present study were to determine total fungal counts and relative density of A. fumigatus in silage samples, and to determine the natural incidence of gliotoxin in silage and ready dairy feed samples. The potential gliotoxin pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 25 publications
4
49
1
2
Order By: Relevance
“…However, Argentinean samples always showed higher F. verticillioides isolation frequency than Brazilian samples. González Pereyra et al (2008) obtained similar with us from finished pig feed samples in central Argentina. However, they did not report the fungal contamination present in raw materials.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…However, Argentinean samples always showed higher F. verticillioides isolation frequency than Brazilian samples. González Pereyra et al (2008) obtained similar with us from finished pig feed samples in central Argentina. However, they did not report the fungal contamination present in raw materials.…”
Section: Discussionsupporting
confidence: 82%
“…These results are similar to those obtained by other researchers in pig samples feed , Gonzalez Pereyra et al 2008. In general, fungal counts in different kinds of animal feed have been recently informed over 1×10 4 UFC g −1 (Gonzalez Pereyra et al 2008;Rosa et al 2009;Pereyra et al 2008;Pereyra et al 2009). The screening of samples for fungal propagules is a useful exercise in itself as an indicator of contamination but also complements the analysis of mycotoxins that could be present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that raw milk products can have high concentrations of pathogenic bacteria, dioxins, heavy metals, hormones, antibiotics and mycotoxins [9][10][11][12][13][14]. Mycotoxins, such as aflatoxins have carcinogenic properties [15,16]. Aflatoxins can be transferred from milk to cheese [17].…”
Section: Introductionmentioning
confidence: 99%